2007
DOI: 10.1016/j.biocel.2006.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte serum-free medium maintains long-term liver gene expression and function in cultured rat hepatocytes by preventing the loss of liver-enriched transcription factors

Abstract: Freshly isolated hepatocytes rapidly lose their differentiated properties when placed in culture. Therefore, production of a simple culture system for maintaining the phenotype of hepatocytes in culture would greatly facilitate their study. Our aim was to identify conditions that could maintain the differentiated properties of hepatocytes for up to 28 days of culture. Adult rat hepatocytes were isolated and attached in Williams’ medium E containing 10% serum. The medium was changed to either fresh Williams’ me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…20%) (Figure 3H and supplementary methods). When cultured in keratinocyte serum free media (KSFM), a media reported to prevent de-differentiation of cultured hepatocytes (Li et al, 2007) we observed conversion efficiencies similar to our regular hepatocyte growth media (Figure S1E,F). …”
Section: Resultssupporting
confidence: 71%
“…20%) (Figure 3H and supplementary methods). When cultured in keratinocyte serum free media (KSFM), a media reported to prevent de-differentiation of cultured hepatocytes (Li et al, 2007) we observed conversion efficiencies similar to our regular hepatocyte growth media (Figure S1E,F). …”
Section: Resultssupporting
confidence: 71%
“…This indicated that the decrease was independent of the incubation system, provided slices did not adhere to the ceiling of the microchamber. Various medium supplements have been shown to improve the maintenance of the metabolic rate for longer periods of time (Agius et al, 1986;Li et al, 2007). It was therefore decided to supplement the medium with 5% v/v heat-inactivated calf serum, as has commonly been done by others when liver slices were incubated longer than 48 h (De Graaf et al, 2007).…”
Section: Phase II Metabolism With Medium Supplementsmentioning
confidence: 99%
“…Because the shortage of viable liver organs available for transplant remains an issue, the use of hepatocyte transplantation and artificial liver devices as alternative therapeutic approaches has been proposed . However, the limited lifespan and proliferative capacity as well as rapid de‐differentiation after hepatocyte isolation may hinder the usefulness of the in vitro hepatocytes for liver transplantation . Recent studies suggested that human embryonic or tissue‐specific adult stem cells could be directed to become functional hepatocyte‐like cells for clinical applications and drug development, although optimal differentiation protocol remained to be determined …”
Section: Introductionmentioning
confidence: 99%
“…1 However, the limited lifespan and proliferative capacity as well as rapid de-differentiation after hepatocyte isolation may hinder the usefulness of the in vitro hepatocytes for liver transplantation. 2,3 Recent studies suggested that human embryonic or tissue-specific adult stem cells could be directed to become functional hepatocyte-like cells for clinical applications and drug development, although optimal differentiation protocol remained to be determined. 4 Human mesenchymal stem (stromal) cells (hMSCs) are currently considered a key cell source for tissue engineering because of their relatively easy access and wider distribution in different parts of the body and great expansion and differentiation potential into various cell lineages.…”
Section: Introductionmentioning
confidence: 99%